Micro Hydro Power Plant (MHP) performance using breast-shot waterwheel with different electrical load to improve efficiency - Herlambang, Yusuf Dewantoro; Bono, Bono; Suwoto, Gatot; Hermawan, Baktiyar Mei; Sumarno, F. Gatot; Margana, Margana; Marliyati, Marliyati (Jurnal Polimesin, 2024)
The aim of this study is to investigate the performance of breast-shot waterwheel with different electrical loads to increase efficiency. The method used is to design a pinwheel blade using blade material with a supporting frame added to the top, middle, and bottom of the pinwheel blade. The blade material used a thickness of 1.5 mm with angle iron installed on the three sides of the blade with a size of 30 mm × 30 mm × 3 mm. Tests were carried out with variations in lamp load when the water flow rate and water velocity were constant. Parameters measured in this test are water flow rate (m3/s), velocity of water (m/s), head of water (m), generator rotation (rpm), electric current (A), and generator output voltage (V). The results of the Hydro Power Plant (MHP) test with a waterwheel drive with the highest efficiency value at a water discharge of 0.267 m3/s, a velocity of 5.069 m/s, a generator rotation of 940 rpm, and a load of 840 W, which is 10.74%.